2019
DOI: 10.1038/s41598-019-52437-6
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations of cloud and relative humidity profiles across the tropics

Abstract: Even though the diurnal cycle of solar forcing on the climate system is well defined, the diurnal evolutions of water vapor and clouds induced by the solar forcing are not yet established across the tropics. Here we combine recent satellite observations of clouds profiles and relative humidity profiles to document the diurnal variations of the water vapor and clouds vertical distributions over all the tropics in June-July-August. While the daily mean water vapor and cloud profiles are different between land an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 44 publications
3
39
0
1
Order By: Relevance
“…However, the solar force exerted by the longer incoming radiation from the sunshine duration corresponds to the RH profile ( Figure 2 c and 2f). The varying seasonal phases or lag of local climatology variables do not exhibit a strong relationship with high cloud amounts ( Chepfer et al., 2019 ).…”
Section: The Brightness Datamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the solar force exerted by the longer incoming radiation from the sunshine duration corresponds to the RH profile ( Figure 2 c and 2f). The varying seasonal phases or lag of local climatology variables do not exhibit a strong relationship with high cloud amounts ( Chepfer et al., 2019 ).…”
Section: The Brightness Datamentioning
confidence: 99%
“…In the convective mechanism, the cold cloud coverage is dominated by spatially large, long-lived cloud systems in the near surface. They tend to form in the early evening (2–7 PM) and reach a maximum areal extent of very cold cloud tops before dawn to early morning (0–6 AM) ( Chen and Houze, 1997 ; Hong et al., 2008 ; Chepfer et al., 2019 ).…”
Section: The Brightness Datamentioning
confidence: 99%
“…Errors in RH and T can make the atmospheric column drier or wetter influencing stability of the atmospheric column and the updraft of air parcels affecting cloud formation by limiting the height of supersaturation of parcels and the amount of convective available potential energy to drive convection [76]. In the tropics, satellite observations have shown that RH and thick clouds vary daily by as much as 20% and 10%, respectively, at any altitude over land [77]. Given RH errors in this study are as much as 20% which can be associated with errors in T [78], it is sufficient to say thick clouds will be influenced significantly during a daily cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to altitude, another fundamental factor is the water vapor contained in the air that evidently contributes with its partial pressure and affects the partial pressure of the other gases in the atmosphere (Wenger et al, 2015). In the real-world atmospheric water vapor concentration varies throughout the day (Chepfer et al, 2019). It can also vary depending on geographic location since it is not the same to live in the most humid regions of the world like the Amazon rainforest or in the driest deserts like the Atacama in South America.…”
Section: Oxygen Availabilitymentioning
confidence: 99%